Sumbangsih al-Amidi dalam Perkembangan Kritik Sastra Arab - Putra, Ringgal Oksa; Ihsan, Muhammad (Universitas Muhammadiyah Gorontalo, 2024)
Al-Amidi was an Arabic literarure critic in the 4th century Hijriah, he suffered a lot from his critical mindset in the form of books, but not much scientific research raised the topic of his research on al-Amidi, especially in Indonesia. The purpose of this study is to look at al-Amidi's scientific background, al-Amidi's contributions in Arabic literature criticism and how writers view al-Amidi. In this study method with library research. Data collection techniques in this study were observing and recording techniques by recording data. The conclusion of this study shows that al-Amidi's scientific background was influenced by previous Ulama in Arabic literary criticism. al-Amidi played a very important role and he was one of the originators of literary analysis with comparative studies although there were still many pros and cons related to al-Amidi's objectivity in assessing Abu Tamam and al-Buhturi.